Physical Education Learning Management in Fostering Students' Kinesthetic Intelligence - Pahrul Rodji, Achmad; Wasliman, Iim; Suhendraya Muchtar, Hendi; Koswara, Nandang (International Journal of Educational Research & Social Sciences, 2022)
Kinesthetic-based physical education learning has a great opportunity to develop multiple intelligences in students at school, Through physical education carried out in schools, it can be used as a tool to help students improve motor skills, health, fitness, character building, personality, discipline and inculcating the values ​​of honesty, cooperation and responsibility. Currently, the reality of teachers in the field does not understand the role of physical education in the educational process, most teachers argue that sport is only for maintaining health and has not yet reached the role of physical education in supporting the development of children's intelligence. The purpose of this study was to see how far the implementation of physical education in improving kinesthetic intelligence in Madrasah Ibtidayyah (MI) Al-Firdaus and MI Yanuri through a management approach. Specifically, this study describes the principles of management theory, including: (1) planning, (2) organizing, (3) implementing, and (4) evaluating physical education and its relationship with kinesthetic intelligence using management theory from GR Terry and Howard Gadner's theory of kinesthetic intelligence. This study uses a descriptive method with a qualitative approach and data collection by conducting observations, interviews, and documentation studies.